2018
DOI: 10.1093/jme/tjy152
|View full text |Cite
|
Sign up to set email alerts
|

Lethal Effects of Silica Gel-Based CimeXa and Kaolin-Based Surround Dusts Against Ixodid (Acari: Ixodidae) Eggs, Larvae, and Nymphs

Abstract: As tick resistance to conventional acaricides becomes more common, alternative control tactics are gaining attention. Insecticidal dusts CimeXa and Surround, based on silica gel and kaolin, respectively, were assessed against Amblyomma americanum (L.) (Ixodida: Ixodidae) eggs, larvae, and nymphs in the laboratory. Coverage by the dry dusts, particularly CimeXa, was strongly lethal to larvae and to a lesser extent to nymphs. Larval mortality was also high when larvae crawled across thin layers of CimeXa and, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 47 publications
0
18
0
1
Order By: Relevance
“…For reducing ixodid populations, Thompson et al [ 200 ] suggested that M. minutiflora and A. gayanus should be planted in infested areas. Fernandez-Ruvalcaba et al [ 201 ], using A. gayanus and M. minutiflora plots, reported that questing R. microplus larvae were 52.1% and 73.3% less abundant than on nonrepellent and nonacaricdial grass species (as determined by flag sampling [ 28 ]). All R. appendiculatus instars avoid climbing on M. minutiflora but not on kikuyu grass, Pennisetum clandestinum Hochst.…”
Section: Botanically-based Substancesmentioning
confidence: 99%
See 4 more Smart Citations
“…For reducing ixodid populations, Thompson et al [ 200 ] suggested that M. minutiflora and A. gayanus should be planted in infested areas. Fernandez-Ruvalcaba et al [ 201 ], using A. gayanus and M. minutiflora plots, reported that questing R. microplus larvae were 52.1% and 73.3% less abundant than on nonrepellent and nonacaricdial grass species (as determined by flag sampling [ 28 ]). All R. appendiculatus instars avoid climbing on M. minutiflora but not on kikuyu grass, Pennisetum clandestinum Hochst.…”
Section: Botanically-based Substancesmentioning
confidence: 99%
“…Kaolin is a porous, fine-grained aluminosilicate white mineral clay that causes a variety of detrimental effects to arthropods [ 28 ]. Kaolin particles adhere to the arthropod integument, occluding the normal range of motion of appendages, strongly obstructing mobility, and they can also abrade the integumentary cuticle, leading to desiccation [ 491 , 492 ].…”
Section: Inert Dustsmentioning
confidence: 99%
See 3 more Smart Citations